2015
DOI: 10.1039/c5ta05350a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and catalytic properties of ZSM-5 zeolite with hierarchical pores prepared in the presence of n-hexyltrimethylammonium bromide

Abstract: Graphical AbstractZSM-5 zeolites with hierarchical pores have been synthesized with n-hexyltrimethylammonium bromide and exhibited superior catalytic performance than the microporous zeolite.ZSM-5 samples with hierarchical pores (macropores, mesopores and micropores) were synthesized in the presence of nhexyltrimethylammonium bromide (HTAB) and tetrapropylammonium hydroxide (TPAOH). The effect of the synthesis conditions including Si/Al ratio, crystallization temperature and time, and the amount of HTAB added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…The decrease of both signals in FmZSM-5 may be due to the presence of partial dealumination and the occurrence of the crystallization process. On the other hand, 29 Si MAS NMR spectra of RmZSM-5 and FmZSM-5 exhibited one main signal (at -114 ppm) typically observed for (≡SiO)4Si species, evidencing the highly structured framework and high crystallinity of the ZSM-5 zeolite [15]. Additionally, a weak shoulder signal at -100 ppm was observed, which assigned for (≡SiO)3Si species.…”
Section: Catalytic Performancementioning
confidence: 92%
“…The decrease of both signals in FmZSM-5 may be due to the presence of partial dealumination and the occurrence of the crystallization process. On the other hand, 29 Si MAS NMR spectra of RmZSM-5 and FmZSM-5 exhibited one main signal (at -114 ppm) typically observed for (≡SiO)4Si species, evidencing the highly structured framework and high crystallinity of the ZSM-5 zeolite [15]. Additionally, a weak shoulder signal at -100 ppm was observed, which assigned for (≡SiO)3Si species.…”
Section: Catalytic Performancementioning
confidence: 92%
“…A mesoporous catalyst is favorable for large molecules like epoxidized canola biodiesel and is anticipated to increase the estolide formation via an oxirane ring opening followed by esterification. Earlier studies [11] disclosed that beyond the Si/Al ratio of 32 in the prepared catalysts indicated the decrease in total pore volume; therefore, in the present study, Si/Al ratio was maintained as 32. Presence of pentasil groups in the catalyst is indicated by the IR band ( Figure 2 Figure 3 shows the NH3-TPD profile of aluminosilicates catalyst.…”
Section: Catalyst Characterizationmentioning
confidence: 49%
“…The moderate and high-intensity desorption regions between the temperatures 300-440 • C and 440-560 • C are due to moderate and strong acidic sites, respectively ( Table 2). The wider desorption peak in the lower intensity area indicates that the zeolite has a higher useful group of weak surface acidic sites [11,15,16]. The XRD pattern of the catalyst is presented in Figure S1.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…The mesopore diameters can be facilely adjusted from 2 nm to 20 nm by changing the chain length of amphiphilic organosilanes [85]. Bai et al [72] prepared scroll-like ZSM-5 zeolite with micropores, mesopores and macropores by layer-by-layer wrapping of zeolite nanosheets with the assistance of n-hexyltrimethylammonium bromide (HTAB). A coulombic interaction existing between HTAB and the negatively charged aluminosilicate species stabilized the zeolite nanoparticles by decreasing their surface free energy, and facilitates the formation of hierarchical ZSM-5 zeolite at short crystallization time.…”
Section: Double Templating With Soft-template Methodsmentioning
confidence: 99%